2014
DOI: 10.1111/jon.12156
|View full text |Cite
|
Sign up to set email alerts
|

Emergent, After Hours Magnetic Resonance Imaging of the Spine

Abstract: Clinical use of emergent after hours spine MRI is steadily increasing at our institution. While MR imaging often discerned significant pathologies, performing these emergent studies rarely resulted in immediate surgical or radiotherapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Previous studies evaluating the radiologic and clinical outcomes of spine MR imaging have generally focused on a single-segment spine study such as cervical or lumbar spine MR imaging. 1,19 Black et al 1 looked at the radiologic and clinical outcomes of 179 emergent spine MRIs during a 13-year period. There were 77 cervical, 87 thoracic, and 101 lumbar spine MR imaging studies, in combination or in isolation, without providing a specific number for TS-MR imaging.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies evaluating the radiologic and clinical outcomes of spine MR imaging have generally focused on a single-segment spine study such as cervical or lumbar spine MR imaging. 1,19 Black et al 1 looked at the radiologic and clinical outcomes of 179 emergent spine MRIs during a 13-year period. There were 77 cervical, 87 thoracic, and 101 lumbar spine MR imaging studies, in combination or in isolation, without providing a specific number for TS-MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…A significant radiologic finding was seen in 104/179 (58%), and 66/179 (36.8%) were treated within 48 hours. 1 Another study by Gardner et al 19 looking only at the lumbar spine for patients with cauda equina syndrome found that 33% of patients with suspected cauda equina syndrome had positive radiologic findings but only 7% received treatment. Both of these studies used different radiologic outcome criteria and different patient populations such as those with mixed single-and multiple-segment MR imaging scans as in the study by Black et al and lumbar spine studies in case of Gardner et al compared with all TS-MR imaging in our study, making it difficult to compare the results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations